Representasi Penyelesaian Konflik Keluarga dalam Drama Korea Queen of Tears - Sabina Hani Farida; Fitria Nur 'Aini (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to examine how family conflict resolution is represented in the 2024 Korean drama Queen of Tears. The research employed a qualitative approach using content analysis, focusing on 16 episodes that highlight family conflict dynamics and resolution strategies. The analysis concentrated on the evolution of communication patterns among characters throughout the storyline. The findings reveal that the drama portrays a transformation from destructive to constructive communication. In the early stages, conflicts are characterized by closed communication, passive-aggressive behavior, triangulation, and false assumptions. However, as the story progresses, these patterns shift toward open, empathetic, assertive, and collaborative communication, allowing for healthier and more adaptive resolutions. Furthermore, the study identifies the influence of Korean cultural values such as jeong (emotional bonds), nunchi (social sensitivity), face-saving, and collectivism in shaping how characters handle conflicts and reach reconciliation. This representation not only reflects the complexity of conflict within the Korean cultural context but also provides audiences with practical models for conflict resolution. Consequently, the drama serves not only as a form of entertainment but also as an educational medium that promotes effective family communication. The findings of this research contribute significantly to studies on family communication, media representation, and popular culture, offering insights into how television narratives can shape perceptions of interpersonal relationships and conflict management strategies.